HDC1 Promotes Primary Root Elongation by Regulating Auxin and K+ Homeostasis in Response to Low-K+ Stress - Xiaofang Kuang; Hao Chen; Jing Xiang; Juan Zeng; Qing Liu; Yi Su; Chao Huang; Ruozhong Wang; Wanhuang Lin; Zhigang Huang (Biology)
Plants frequently encounter relatively low and fluctuating potassium (K+) concentrations in soil, with roots serving as primary responders to this stress. Histone modifications, such as de-/acetylation, can function as epigenetic markers of stress-inducible genes. However, the signaling network between histone modifications and low-K+ (LK) response pathways remains unclear. This study investigated the regulatory role of Histone Deacetylase Complex 1 (HDC1) in primary root growth of Arabidopsis thaliana under K+ deficiency stress. Using a hdc1-2 mutant line, we observed that HDC1 positively regulated root growth under LK conditions. Compared to wild-type (WT) plants, the hdc1-2 mutant exhibited significantly inhibited primary root growth under LK conditions, whereas HDC1-overexpression lines displayed opposite phenotypes. No significant differences were observed under HK conditions. Further analysis revealed that the inhibition of hdc1-2 on root growth was due to reduced apical meristem cell proliferation rather than cell elongation. Notably, the root growth of hdc1-2 showed reduced sensitivity compared to WT after auxin treatment under LK conditions. HDC1 may regulate root growth by affecting auxin polar transport and subsequent auxin signaling, as evidenced by the altered expression of auxin transport genes. Moreover, the organ-specific RT-qPCR analyses unraveled that HDC1 negatively regulates the expression of CBL-CIPK-K+ channel-related genes such as CBL1, CBL2, CBL3, AKT1, and TPK1, thereby establishing a molecular link between histone deacetylation, auxin signaling, and CBLs-CIPKs pathway in response to K+ deficiency.